The prince of Frogtown - Bragg, Rick. (New York : Alfred A. Knopf, 2008)
Rick Bragg closes his circle of family stories with a tale of fathers and sons inspired by his own relationship with his ten-year-old stepson. Having married a mother, he discovers that he is unsuited to fatherhood, to this boy in particular, a boy accustomed to love and affection rather than violence and neglect--a boy wholly unlike the child Rick once was. With the weight of this new boy tugging at him, Rick sets out to understand his father, his son, and himself. The book documents a journey back in time to the Alabama landscape of Rick's youth, and to a troubled, charismatic hustler, Rick's father, a man bound to bring harm even to those he truly loves. Bragg delivers a moving rumination on the lives of boys and men, a poignant reflection on what it means to be a father and a son.--From publisher description.
In a cloud of smoke -- The village -- Bob -- Fearless -- The bootlegger's rhythm -- Flying Jenny -- My fair Orvalene -- The hanging -- Chicken season -- What you're supposed to do -- At least a hundred dollars then -- Ross -- Dallas -- Ride -- One friend -- Amen -- The circle.
"A Borzoi book."
Keywords: Bragg, Rick; Fathers and sons; Stepfathers; Journalists -- United States; Working class whites -- Alabama; Alabama